Effects of miniature filaments on flow characteristics - Yeo, Jun Xiong (2018)
It is important to understand how the aerodynamic properties can be influenced by fabrics significantly for various type of high speed sports. Thus, it is important to design aerodynamically efficient sport fabrics to enhance the athletes’ performance. This project presents experimental investigation on five different fabrics using a designed cylindrical methodology to study the effect of miniature filaments on flow characteristics. Drag force were measured on a circular cylinder covered with different fabrics, carried out in the wind tunnel, to determine the effects of the aerodynamic behaviour. Non-dimensional drag coefficient and Reynolds numbers were also applied to specify how a variety of fabrics with different textures can potentially affect the flow transition. The physical surface parameters were determined using electron scanning microscope and the surface profile were measured by the automatic surface profilometer, Talyscan 150. A correlation between the aerodynamics properties and fabric surface characteristic (surface roughness) was established. From the experimental results, no sign of drag reduction is observed when smooth cylinder was used for set-up. Enhancement of drag reduction was noted when all fabrics were used in place by covering the smooth cylinder set-up. The highest enhancement came from white fabric with enhancement up to 53.19% drag reduction as compared to other fabrics. These experimental methodologies and their relationships proved that the fabric characteristics played a crucial role in enhancing the aerodynamic properties by reducing the overall drag of the athletes.